2015
DOI: 10.2106/jbjs.n.00983
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Pulseless Pediatric Supracondylar Humeral Fracture

Abstract: A pediatric supracondylar humeral fracture with a pulseless, poorly perfused hand requires emergency operative reduction. If the limb remains pulseless and poorly perfused after fracture fixation, vascular exploration and possible reconstruction is necessary. A pediatric supracondylar humeral fracture with a pulseless, well-perfused hand should be treated urgently with operative fixation of the fracture and subsequent reassessment of the vascular status. Controversy exists regarding the optimal management of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 37 publications
1
67
0
12
Order By: Relevance
“…If the initial attempt is unsuccessful in restoring the pulse, open reduction and vascular exploration is mandated [19]. Management of children with absence of their radial pulse with a well-perfused hand is still controversial [1921]. Remarkably, no difference between early surgical treatment (8 hours or less following injury) and delayed surgical treatment (more than 8 hours following injury), with regard to the perioperative complication rates, is reported [22].…”
Section: Discussionmentioning
confidence: 99%
“…If the initial attempt is unsuccessful in restoring the pulse, open reduction and vascular exploration is mandated [19]. Management of children with absence of their radial pulse with a well-perfused hand is still controversial [1921]. Remarkably, no difference between early surgical treatment (8 hours or less following injury) and delayed surgical treatment (more than 8 hours following injury), with regard to the perioperative complication rates, is reported [22].…”
Section: Discussionmentioning
confidence: 99%
“…Color duplex scanning and ultrasound velocimetry have been shown to have some benefit in evaluating children for vascular injury and in evaluating the possible need for vascular exploration. 23,24 Other studies have confirmed that patients with a pink hand with capillary refill (and no palpable or Doppler pulses) after reduction and pinning can be safely observed 25,26 ; however, some of these children develop evidence of worsening ischemia and require exploration and thus close observation is paramount. Many authors have noted the association between neurologic deficit and vascular injury in these fractures, and the absence of return of median nerve function in the forearm and hand after CRPP may be an indication for surgical exploration.…”
Section: Other Causes Of Closed Arterial Damagementioning
confidence: 97%
“…Nesse caso, é prudente solicitar a presença de cirurgião vascular ou microcirurgião para possível reconstrução arterial. 8 O acesso transverso anterior é o recomendado, podendo ser ampliado para distal ou proximal e permitindo exploração direta do feixe neurovascular e reconstrução da artéria braquial quando necessário. 1,4 Na ausência de laceração ou transecção, o aquecimento do membro e aplicação de papaverina ou lidocaína tópica pode ajudar a diminuir o espasmo arterial.…”
Section: Rev Bras Ortopunclassified